THE CORRUPTION AND HUMAN DEVELOPMENT TO THE ECONOMIC GROWTH OF OIC COUNTRIES - Kurniawan, Yusuf; Ratnasari, Ririn Tri; Mustika, Hindah (Universitas Airlangga, 2020)
This paper aims to estimate the effect of corruption (represented by data of Corruption Perception Index) and human development (represented by data of Human Development Index) on the economic growth (represented by data of Gross Domestic Product) in 44 (forty-four) countries who join the Organization of Islamic Cooperation (OIC). this paper uses multiple linear regression with panel data of Corruption Perception Index from transparency.org, Human Development Index from United Nations Development Program (UNDP) and Gross Domestic Product from World Bank. The 10 years range of data (2009-2018) finds the Corruption Perception Index does not have a significant effect on the economic growth, but The Human Development Index has a positive significant effect on the economic growth or Gross Domestic Product. It can be seen that the commitment of OIC countries in human development is on the right path, since they are in line with their economic growth rates. When viewed together, the Corruption Perception Index and the Human Development Index have a simultaneous influence on the economic growth. So, this result is important to help the OIC as additional references to their Annual Summit or Conference to focus more on Human Development strategy to enhance the economic growth.